Culture Isolate of Rickettsia felis from a Tick - Danchenko, Monika; Benada, Oldřich; Škultéty, Ľudovít; Sekeyová, Zuzana (International journal of environmental research and public health, 2022)
Although the cat flea, Ctenocephalides felis, has been identified as the primary vector of Rickettsia felis, additional flea, tick, mite, and louse species have also been associated with this bacterium by molecular means; however, the role of these arthropods in the transmission of R. felis has not been clarified. Here, we succeeded in culture isolation of R. felis from a host-seeking castor bean tick, Ixodes ricinus, the most common tick in Slovakia. The bacterial isolation was performed on XTC-2 cells at 28 °C using the shell-vial technique. An evaluation of the growth properties was performed for both the XTC-2 and Vero cell lines. We observed R. felis in the infected host cells microscopically by Gimenez staining and immunofluorescence assay. The R. felis isolate was purified by gradient ultracentrifugation and visualized by electron microscopy. Fragments of the genes gltA, ompA, ompB, htrA, rpoB, sca4, rffE, and rrs were amplified and compared with the corresponding sequences of the type strain URRWXCal2 and other R. felis culture -isolated strains. We did not detect any nucleotide polymorphisms; however, plasmid pRFδ, characteristic of the standard strain, was absent in our isolate. Herein, we describe the first successful isolation and characterization of a tick-derived R. felis strain "Danube", obtained from an I. ricinus nymph.
Keywords: Ixodes ricinus; cell culture; shell-vial technique; vector-borne bacteria; Cell Line; klíště; Rickettsia; buněčné linie; zvířata; Arthropods; Ixodes; Rickettsia felis; členovci; Animals